2008
DOI: 10.1002/syn.20496
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes for normalization: A study of rat brain tissue

Abstract: Quantitative real-time polymerase chain reaction (qPCR) has become a widely used tool in the search for disease genes. When examining gene expression with qPCR in psychiatric diseases, endogenous reference gene(s) must be used for normalization. Traditionally, genes such as beta-actin (ActB), Gapd, and 18s rRNA, assumed to be stably expressed, have been used for normalization. However, it has become clear that expression of these genes is influenced by different experimental paradigms. Since stable gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(124 citation statements)
references
References 18 publications
1
120
1
2
Order By: Relevance
“…This indicated that these HKGs are not good macrophage reference genes; these results also indicated that the expression of these genes could be reshaped by various ECM components present in culture, or be sensitive to adhesion-specific signaling. Previous studies have also reported divergent qPCR results for ACTB in rat oligodendrocytes and rat brain tissue (Bonefeld et al, 2008;Nelissen et al, 2010) and B2M in human heart tissues (Molina et al, 2014). These findings emphasize the importance of evaluating all genes used for normalization, even if they are traditionally used in other studies (Nelissen et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…This indicated that these HKGs are not good macrophage reference genes; these results also indicated that the expression of these genes could be reshaped by various ECM components present in culture, or be sensitive to adhesion-specific signaling. Previous studies have also reported divergent qPCR results for ACTB in rat oligodendrocytes and rat brain tissue (Bonefeld et al, 2008;Nelissen et al, 2010) and B2M in human heart tissues (Molina et al, 2014). These findings emphasize the importance of evaluating all genes used for normalization, even if they are traditionally used in other studies (Nelissen et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Relative expression of the genes of interest was calculated after obtaining the corresponding Ct values and correcting for unequal sample input using geNorm (Vandesompele et al, 2002), which identifies the two most stably expressed housekeeping genes (Ywhaz and CycA) from a set of three tested candidate genes reported previously to be stably expressed in the brain (Bonefeld et al, 2008) to calculate a normalization factor for each sample. This normalization factor was then used to obtain the relative differences between the samples for each primer pair.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of each transcript was normalized to the amount of Gapdh expressed in the same sample. For stability comparison of candidate reference genes, we applied the NormFinder Software (http://www.mdl.dk; Andersen et al 2004, Bonefeld et al 2008. All samples were analyzed in duplicates.…”
Section: Rt-pcrmentioning
confidence: 99%